![\sqrt{1 + cosa \frac{ \sqrt{1 + cos a} } = cosec a + cot a \sqrt{1 + cosa \frac{ \sqrt{1 + cos a} } = cosec a + cot a](https://tex.z-dn.net/?f=+%5Csqrt%7B1+%2B+cosa+%5Cfrac%7B+%5Csqrt%7B1+%2B+cos+a%7D++%7D++%3D+cosec+a+%2B+cot+a)
Answers
Answered by
0
Answer:
Prove:
1+cos A
1−cos A
=cosec A−cot A
ANSWER
1+cosθ
1−cosθ
=cosecθ−cotθ
L.H.S Rationalizing,
1−cos
2
θ
(1−cosθ)
2
=
1−cos
2
θ
1−cosθ
=
sin
2
θ
1−cosθ
=
sinθ
1−cosθ
=
sinθ
1
−
sinθ
cosθ
=cosesθ−cotθ
=R.H.S
∴ L.H.S=R.H.S
Hence proved.
Similar questions